2017
DOI: 10.1007/s00520-017-3591-1
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and adherence to an online intervention for cancer-related distress: older age is not a barrier to adherence but may be a barrier to uptake

Abstract: Uptake and adherence to an online intervention for cancer-related distress: older age is not a barrier to adherence but may be a barrier to uptake. 2Uptake and adherence to an online intervention for cancer-related distress: older age is not a barrier to adherence but may be a barrier to uptake. Abstract PurposeWhile online interventions are increasingly explored as an alternative to therapist-based interventions for cancer-related distress, limitations to efficacy potentially include low uptake and adherenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 43 publications
6
39
2
Order By: Relevance
“…Therefore, our study does not confirm the concern that adherence in mHealth interventions is in general poor, which would limit treatment implementation. The adherence of our patients is also comparable with recent research on adherence to e-and mHealth interventions for cancer patients [32,33]. A study by Beatty el al.…”
Section: Summary Of Findingssupporting
confidence: 74%
See 3 more Smart Citations
“…Therefore, our study does not confirm the concern that adherence in mHealth interventions is in general poor, which would limit treatment implementation. The adherence of our patients is also comparable with recent research on adherence to e-and mHealth interventions for cancer patients [32,33]. A study by Beatty el al.…”
Section: Summary Of Findingssupporting
confidence: 74%
“…With 74%, mainly female patients enrolled in this study, which is consistent with characteristics of mHealth users in other studies with 84% female patients [46] and 54% female patients [47]. The mean age of participating patients was 53 years; this is comparable to other face-to-face mindfulness and relaxation interventions [48] or online interventions for cancer patients [32]. The interviews showed that the patients were satisfied with the app in general.…”
Section: Summary Of Findingssupporting
confidence: 72%
See 2 more Smart Citations
“…Age appeared to play a role in preferred choice of device as younger cancer survivor users anticipated preferring smartphones due to easy access, while some of the older patient users (> 50-years) anticipated preferring to use tablets due to the smaller smartphone screens. Older age has been reported to be a barrier to uptake of web-based intervention for cancer-related distress [46]. However, once enrolled, older individuals have demonstrated better intervention adherence.…”
Section: User Requirementsmentioning
confidence: 99%